Penegakan Hukum Terhadap Anak Yang Menjadi Tindak Pidana Perdagangan Orang di Kota Tanjungpinang - Widiyani, Heni; Dewi, Intan Kumala; Alifiantri, Deswita; Lubis, Dian Putri Patrecia; Rinaldy, Estabella; Lubis, Dara Akika Yuzani; Purnomo, Armando Tri Cahyo; Efritadewi, Ayu (Wajah Hukum, 2024)
Children are buds, as well as the next generation of young people who have special positions, characteristics and dispositions that ensure the continuity of the nation's existence in the future. Protection efforts are needed to realize children's welfare by distributing guarantees for the fulfillment of their rights and treatment without discrimination. This study aims to describe how legal protection for children as victims of trafficking is based on Law No. 35 of 2014 concerning Child Protection and how sanctions are imposed on perpetrators of child trafficking crimes. The research method used in this study is normative juridical research. The results of this study show the legal protection of children as victims of trafficking based on Law No. 35 of 2014 concerning Child Protection and dignity, and recognition of human rights owned by children. Not only that, sanctions against child trafficking offenders are regulated in Law No. 21 of 2007 concerning the Eradication of Trafficking in Persons.